Numerical Analysis on the Performance of High Concentration Photovoltaic Systems Under the Nonuniform Energy Flow Density - Chen, Haifei; Wang, Yunjie; Ding, Yuwei; Cai, Baorui; Yang, Jie (Frontiers in Energy Research, 2021)
Photovoltaic panels can directly convert solar energy into electricity, but temperature will have a certain impact on the efficiency of photovoltaic cells. Especially under the condition of non-uniform energy flow density of high power concentration, it is of great significance to maintain the temperature uniformity of cells. Therefore, based on the radiation under non-uniform heat flux density, four heat exchangers were proposed including single-channel serpentine flow, multi-channel flat plate, full jet and single-jet nozzle. Taking into account the uniformity of the cell temperature, the single-jet nozzle and single-channel serpentine flow can better maintain the uniformity of the temperature field compared with other heat exchangers. Especially under high-concentration energy flow density, considering the quality of heat and electricity, the performance of the four-jet nozzles is the best from the perspective of exergy efficiency. Under the condition of four-jet nozzles, the electrical efficiency and thermal efficiency of the cell can be maintained at about 29% and 62.5%, respectively, and the exergy efficiency of the system can reach 31%.